TRICIN: A Phase II Trial on the Efficacy of Topical TRIchloroacetic Acid in Patients with Cervical Intraepithelial Neoplasia - Schwameis, Richard; Ganhoer-Schimboeck, Julia; Hadjari, Victoria Laudia; Hefler, Lukas; Bergmeister, Birgit; Küssel, Tatjana; Gittler, Gunda; Steindl-Schoenhuber, Theodora; Grimm, Christoph (Cancers, 2022)
Data on non-surgical treatment approaching persistent cervical intraepithelial neoplasia (CIN) are scarce. Retrospective analysis suggest high efficacy of topical treatment with trichloroacetic acid (TCA). This prospective phase II study set out to investigate the efficacy of a single application of 85% TCA in the treatment of CIN I/II. Patients with CIN I/II were treated a single time with 85% TCA. After three and six months colposcopic, histologic, and HPV evaluation was performed. The primary endpoint was treatment efficacy defined as complete histologic remission six months after treatment. The secondary endpoint was HPV clearance six months after treatment. A total of 102 patients with CIN I/II were included into this trial. Complete histologic remission rates were 75.5% and 78.4% three and six months after TCA treatment, respectively. Clearance rates of HPV 16, 18 and other high risk types were 76.5%, 91.7%, 68.7% after six months, respectively. Side effects of TCA were mild and lasted usually less than 30 min. This is the first prospective trial reporting high histologic complete remission rates in patients with CIN I/II after a single 85% TCA treatment. In the future, TCA may represent an effective and feasible non-surgical treatment approach for CIN.